HUBUNGAN REWARD DENGAN PERILAKU CARING PERAWAT PELAKSANA DI RUANG RAWAT INAP RSUD AJIBARANG - Tri Sumarni; Yuris Tri Naili (Universitas Harapan Bangsa Purwokerto, 2017)
Nurses caring behavior is one of the essential components of the quality of hospital services. Organizational culture can influence the practice of caring behavior. Reward is one of components in the organization's culture. Patient satisfaction survey results indicated a lack of caring behavior in nurses in inpatient section Ajibarang hospital. This study aims to determine the relationship of reward with the behavior of caring nurses in inpatient hospitals Ajibarang. The study design was cross-sectional quantitative approach. Data were collected questionnaire to 41 nurses in May-June 2016 for inpatient section class III Ajibarang hospital. Data analysis included univariate, bivariate with chi square test. Results of univariate analysis showed that most nurses perceiving good reward (73.2%) and good caring behavior (58.5%). The bivariate analysis showed there is no associated between reward with nurses caring behavior (p = 0.303). Bidang Keperawatan Ajibarang Hospital expected caring behavior-related training and insert items into the standard procedur operational and caring nurse performance appraisal. Keywords: Reward, Caring Behavior